Adherence to Therapeutic Regimen in Diabetic Patients Attending a Tertiary Level Hospital - Shrestha, Krishna D; KC, Takma; Ghimire, Rachana (Journal of Institute of Medicine Nepal, 2020)
Introduction Adherence to treatment regimen among diabetes patients is very crucial for good glycemic control. Poor adherence is a widely recognized problem causing great impact on poor health outcomes and healthcare costs. Hence, this study was conducted to identify the adherence to prescribed therapeutic regimen among diabetic patients. Methods A descriptive cross sectional research design was adopted. Data was collected purposively among 422 respondents attending at medical OPD in Tribhuvan University Teaching Hospital through interview using structured questionnaire. Analysis was done by descriptive and inferential statistics. Results The study findings revealed good follow up adherence (57.8%). Adherence to medicine, diet and exercise were (28.5%), (16.1%) and (8.8%) respectively. Dietary adherence was associated with sex (p=0.03), educational level (p<0.001), occupation (p=0.04), attending diabetic counseling (p<0.001) and knowledge level (p<0.001). Exercise adherence was associated with sex, educational level, attending diabetic counseling, history of hospitalization and knowledge level (p<0.05). Medication adherence was associated with attending diabetic counseling (p=0.03). Follow up adherence was associated with education, occupation, attending diabetic counseling, duration of diabetes mellitus, frequency of follow up visit, and knowledge level (p<0.05). Moreover, respondents with good adherence to exercise (75.7%), medicine (63.3%) and follow up adherence (66%) had controlled fasting blood sugar level (p=0.01, p=0.03 and p=0.01 respectively). Conclusion Adherence on diet and exercise was very low than other components among diabetes patients. So, it is recommended to focus on education especially on diet and exercise adherence which would be of great benefit in glycemic control.